Combining Preoperative and Postoperative Inflammatory Indicators Can Better Predict the Recurrence of Hepatocellular Carcinoma After Partial Hepatectomy - Wu M; Yang S; Feng X; Li C; Liu X; Zhang Z; Xiao Y; Liu C; Dong J (Dove Medical Press, 2021)
Meilong Wu,1,2,* Shizhong Yang,1,2,* Xiaobin Feng,1,2 Chengquan Li,1,2 Xiangchen Liu,1,2 Zhenyu Zhang,1,2 Ying Xiao,1,3 Chuchu Liu,4 Jiahong Dong1,2 1School of Clinical Medicine, Tsinghua University, Beijing, 100084, People's Republic of China; 2Hepato-pancreato-biliary Center, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, Beijing, 102218, People's Republic of China; 3Department of pathology, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, Beijing, 102218, People's Republic of China; 4Hepato-pancreato-biliary Surgery of Affiliated Hospital of Qinghai University, Affiliated Cancer Hospital of Qinghai University, Xining, Qinghai, 810001, People's Republic of China*These authors contributed equally to this workCorrespondence: Jiahong DongHepato-pancreato-biliary Center, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, No. 168 Litang Road, Changping District, Beijing, 102218, People's Republic of ChinaTel/Fax +86-10-56118888Email dongjiahong@mail.tsinghua.edu.cnPurpose: Previous studies have shown that various preoperative inflammatory indicators can predict the prognosis of hepatocellular carcinoma (HCC), but the role of postoperative inflammatory indicators remains unclear. This study aimed to explore the prognostic value of postoperative inflammatory indicators and whether combining preoperative and postoperative inflammatory indicators can improve the predictive performance of the prognostic model.Patients and Methods: Eighty-eight patients with primary HCC were included in this study. A preoperative model, postoperative model, and combined model that integrated preoperative and postoperative inflammatory indicators were established. The prognostic value of the models was evaluated by the area under the curve of time-dependent receiver operating characteristic curves (td-AUC).Results: Multivariate analysis of preoperative and postoperative inflammatory indicators and clinicopathological indicators found that tumor number, alpha-fetoprotein (AFP) level, and the preoperative platelet-lymphocyte ratio (prePLR), preoperative prognostic nutritional index (prePNI), and postoperative neutrophil-lymphocyte ratio (postNLR) were independent prognostic factors for the disease-free survival. The prognostic efficacy of the postNLR at 2 years and 3 years was better than that of tumor number, AFP level, and the prePLR, and prePNI. The combined model had higher td-AUC values than the preoperative model, postoperative model, American Joint Committee on Cancer 8th edition stage, and Barcelona Clinic Liver Cancer stage at 2 years (0.814 vs 0.754, 0.765, 0.513 and 0.527, respectively), and 3 years (0.786 vs 0.749, 0.753, 0.509 and 0.529, respectively). The predictive performance of the combined model was better than that of the preoperative model, postoperative model, and traditional clinical stage.Conclusion: Postoperative inflammatory indicators were valuable prognostic indicators. The combination of preoperative and postoperative inflammatory indicators improved the predictive performance of the prognostic model. We should pay more attention to postoperative inflammatory indicators.Keywords: hepatocellular carcinoma, inflammation, postoperative, neutrophil-lymphocyte ratio, disease-free survival